DEVELOMENT OF THE A TELEOBSERVATION MEDIC MODULE IN TELEMEDICINE SYSTEM AT MAJALAYA REGIONAL GENERAL HOSPITAL - Abadi, Iwan; Ilman, Benie (Proceedings of KNASTIK, 2012)
This paper aims to describe a development of teleobservation medic module. Thismodule is a module that was developed in the development of telemedicine systems atMajalaya Regional General Hospital. Some of the reason why Majalaya RegionalGeneral Hospital develop telemedicine system, including the geographical areaMajalaya and desire to make hospital management Majalaya become one of hospitalsin the utilization of information technology (internet technology) in all its activities.Teleobservation medic assisting the physician in making observations on patients,especially patients who are in the ICU. Doctors can take immediate action againstpatients who are in critical condition, though at the time the doctor was no longer inMajalaya Regional General Hospital environment. Software developed from this resultsof this research, showing a display screen with two windows. One windows displays thepatient’s condition that reads information from the patien monitor. Another videowindows displays the patient’s physical condition in real times.